Website Evaluation of DISPERDAG Section of the Average Price of Standard Needs Using the WEBQUAL 4.0 Method - Saifulloh Saifulloh; Isti Indana Zulfa (International Journal of Advances in Data and Information Systems, 2023)
DISPERDAG of Madiun City is one of the organizations that has utilized technology. The community can easily access and get price updates for basic necessities at Pasar Besar City of Madiun. The Internet helps support strong governance management, which benefits its effectiveness. Its functions include making it easier to get information, access public services, communicate with the public, and others. DISPERDAG aims to continue to provide quality services. The quality of services provided to the public must complement the implementation of website-based services so that the public continues to use SISKAPERBAPO services. To provide the best service to users, government institutions should prioritize service quality. Therefore, the success of the service quality of the SISKAPERBAPO website has not been known as long as the website is implemented. This is because there has never been an evaluation of website quality based on user satisfaction. It goes without saying that a website that is useful for assisting users in obtaining information must maintain quality in terms of information delivery and user interaction. Good service quality is offered from the user's point of view as well as the service provider's point of view.